Effects of COVID-19 Pandemic on Changes in Nutritional Status and Physical Activities of School-Age Children: A Scoping Review - Nugroho, Fajar; Ruchaina, Annisa Nafilata; Wicaksono, Angga Galih Luhur (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2022)
This study's objective is to review the consequence of the COVID-19 epidemic on physical activities, sedentary lifestyles, screen time, and changes in the nutritional status of school-age children. The outcomes of this study are intended to be applicable to obesity management in children. This study reviewed full-text articles and open-access publications on the sedentary lifestyle of children during the pandemic. and the data were analyzed using cohort, case-control, and cross-sectional designs. The results of reviewing 17 articles show that school-age children’s physical activities and nutritional status have decreased, but their sedentary lifestyle and screen time have increased due to social restrictions during the COVID-19 pandemic. Children’s decreased physical activities are caused by the absence of a comparable replacement mechanism as that before the pandemic. Meanwhile, the increasingly sedentary lifestyle highly influences children’s physical and mental health. Screen time has also increased and is unavoidable during the pandemic because children’s activities were limited and their learning systems are switched to online learning; as a result, their supporting sedentary lifestyle increases while physical activities decrease. These factors have changed the nutritional status of children during the pandemic. These results support the idea that the pandemic will impact the health of school-age children, especially their nutritional status. This review concludes that it is important to establish policies that prevent children’s further health effects, such as obesity, caused by COVID-19.